PELATIHAN PENGOLAHAN DODOL PISANG BAGI KELOMPOK PENGGERAK DI DUSUN KANDEMENG SULAWESI BARAT - Putra, Reski Praja; Mukhlis, Andi Muhammad Akram; Sukainah, Andi; Indrayani, Indrayani; Rahmah, Nur (Education and Talent Development Center of Indonesia, 2025)
Kandemeng Hamlet is situated in Batulaya Village, Tinambung District, within the Polewali Mandar Regency of West Sulawesi. In this sub-district, bananas are the primary fruit commodity, with production reaching 1,648 quintals in 2023. However, the process of transforming bananas into value-added products remains suboptimal. The aim of this community service initiative is to train the local community on effective techniques for making banana dodol and to develop and optimize banana dodol products that possess greater economic value. The initial phase of this project involves observations, interviews, and discussions with community members to identify the challenges faced by Kandemeng Hamlet. The residents are eager to learn how to process bananas into products with a longer shelf life to enhance the economic value of their banana crops. The proposed solution is to process bananas into banana dodol. The activities will include informational sessions, demonstrations, hands-on assistance, and evaluations. The main ingredients for this training are ambon bananas, coconut milk, glutinous rice flour, rice flour, brown sugar, milk, and vanilla. These ingredients are cooked over medium heat until the mixture reaches the right consistency, indicated by a non-sticky texture, a soft consistency, and a shiny surface resulting from the coconut milk oil. Following assessments and evaluations, participants from the community service activities, specifically the movement group in Kandemeng Hamlet, have successfully produced banana dodol independently. The banana dodol they created has been favored for its sensory qualities, including taste, aroma, texture, and color.